ADAR RNA Modifications, the Epitranscriptome and Innate Immunity - Quin, Jaclyn; Sedmík, Jiří; Vukić, Dragana; Khan, Anzer; Keegan, Liam P; O'Connell, Mary A (Trends in biochemical sciences, 2021)
Modified bases act as marks on cellular RNAs so that they can be distinguished from foreign RNAs, reducing innate immune responses to endogenous RNA. In humans, mutations giving reduced levels of one base modification, adenosine-to-inosine deamination, cause a viral infection mimic syndrome, a congenital encephalitis with aberrant interferon induction. These Aicardi-Goutières syndrome 6 mutations affect adenosine deaminase acting on RNA 1 (ADAR1), which generates inosines in endogenous double-stranded (ds)RNA. The inosine base alters dsRNA structure to prevent aberrant activation of antiviral cytosolic helicase RIG-I-like receptors. We review how effects of inosines, ADARs, and other modified bases have been shown to be important in innate immunity and cancer.
Keywords: přirozená imunita; RNA Editing; RNA editing; RNA, Double-Stranded; dvouvláknová RNA; proteiny vázající RNA; lidé; double-stranded RNA (dsRNA); antiviral responses; interferon; adenosindeaminasa; autoinflammatory disease; editace RNA; Immunity, Innate; pattern recognition receptors (PRRs); RNA-Binding Proteins; transkriptom; Adenosine Deaminase; Transcriptome; Humans